The Implementation of Teachers’ Pedagogical and Professional Competence in Authentic Assessment - Faizah, Annisa; Sutopo, Djoko (Universitas Negeri Semarang, 2021)
This study aims to explain the teacher’s pedagogical competence and professional competence on EFL, authentic assessment on EFL, describe the application of authentic assessment, and investigate the effect of teachers' pedagogical and professional competencies on authentic assessment practice. This qualitative study investigated the effects of pedagogical and professional competencies on authentic assessment practice. The subjects of the study consisted of the English teachers of Public Senior High School 1 Jepara. The data were collected with the observation checklist, questionnaire, and interview. The data were analyzed with Miles and Huberman's model. The teacher manifested her pedagogical competence into the plan implementation, evaluation, and reflection. The way she applied authentic assessment was only with the project. She was aware of the function of authentic assessment. It was proven that she did not level up the learning activities when the learners had not passed a specific criterion she determined. However, since she did not provide corrective feedbacks, the learners felt that the teacher only assessed the final project product. Moreover, the teacher did not provide a proper evaluation. She only provided the correct examples, so it made the learners could not arrange their plans. This situation could be improved if the teacher continuously developed her academic qualification and competence based on science, technology, and artistic advancement. Teachers should have this features to be more professional.